Parents’ educational practices on unacceptable behaviour of preschool children (Training and Practice : Journal of Educational Sciences, 2020)
The research on the frequency of the use of parenting practices in the situations of unacceptable behaviour of preschool children was conducted on a sample of 350 parents. The possible links between parenting practices and some parental demographic indicators were also investigated (gender, educational status, financial status, residential status, number of children in the family, number of family members). Research results show that nearly one third of parents use inadequate educational practices. Some parents’ rearing practices are characterized by the absence of a reaction to children’s unacceptable behaviour, by objecting, threatening, raising voice, abolishing privileges and corporal punishment. The financial and housing status of parents, the number of members in the family and the number of children have statistically significantly influenced the frequency of the implementation of some parenting practices. The obtained data point to the need for comprehensive and continuous support for parents in the development of parental skills.